Analysis of strategy implementation process and employees’ performance in construction companies - Faza Ihsan Zaidi,; Emma Marinie Ahmad Zawawi, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Strategic planning is an effective decision-making tool that has been used for years. Strategy implementation is the most challenging stages in strategic planning. It can influence the company performance which includes the employees’ performance. However, there is still insufficient evidences proves this relationship. Successful strategy implementation process includes understanding of vision and mission, strategic action plan, resources allocation, employees training, employees involvement in decision making, reward system and corporate culture. Strategy implementation can influences the employees’ performance through employees’ commitment, retention and growth. The aim of this research is to analyse the relationship between strategy implementation process and employees’ performance in construction companies. Respondents were G7 contractors in Klang Valley, Selangor. Questionnaire survey were collected and Pearson’s correlation analysis proves that strategy implementation process does influence the employees’ performance in construction companies. Employees’ retention and employees’ growth has strong correlation coefficient, but employees commitment correlation is quite weak. This research is suitable to be used as strategy implementation reference for management team in conducting strategy implementation.